Carbon ion radiotherapy in a hypofractionation regimen for stage I non-small-cell lung cancer - Takahashi, Wataru (Oxford University Press, 2014)
Introduction: In 1994, we started carbon-ion radiotherapy (CIRT) for peripheral stage I non-small-cell lung cancer (NSCLC). First, two phase I/II clinical trials demonstrated the optimal doses of 90.0 GyE in 18 fractions over 6 weeks (Protocol 9303) and 72.0 GyE in 9 fractions over 3 weeks (Protocol 9701) for achieving more than 95% local control with minimal pulmonary toxicity. As a next step, we conducted two successive phase II trials. The first trial (Protocol 9802) used a regimen of 72 GyE per 9 fractions over 3 weeks and the second trial (Protocol 0001) used a regimen of 4 fractions over 1 week, at a fixed dose of 52.8 GyE for stage IA and 60 GyE for IB. In these Phase II trials, the local control rate (LCR) for all patients was 91.5%, and those for T1 and T2 tumors were 96.3 and 84.7%, respectively. The 5-year cause-specific survival rate (CSS) was 67.0% (IA: 84.4, IB: 43.7), and overall survival (OS) was 45.3% (IA: 53.9, IB: 34.2). No adverse events greater than grade 2 occurred in the lung.